Association Between Self-reported Prenatal Cannabis Use and Maternal, Perinatal, and Neonatal Outcomes. Issue 2 (June 2020) - Corsi, D.; Walsh, L.; Weiss, D.; Hsu, H.; El-Chaar, D.; Hawken, S.; Fell, D.; Walker, M.
Abstract : ( JAMA . 2019;322:145–152) The rate of cannabis use among pregnant women in Canada was 2% in 2017. With recent legalization, it is anticipated that cannabis use among pregnant women will continue to rise. Cannabinoids can cross the placenta and enter the fetal blood supply. Previous studies have demonstrated a relationship between pregnant mothers who use cannabinoids and increased incidence of low birth weight, small for gestational age (SGA), stillbirth, and admission to neonatal intensive care. The aim of this study was to evaluate associations between reported prenatal cannabis use and maternal, perinatal, and neonatal outcomes.